Оцінка гідрографічної мережі району річковог басейну Вісли (Західного Бугу та Сяну) на території України згідно типології Водної рамкової директиви ЄС - Хільчевський, Валентин Кирилович; Гребінь, Василь Васильович; Забокрицька, Мирослава Романівна; Khilchevskyi, Valentyn K.; Hrebin, Vasyl V.; Zabokrytska, Myroslava R. (Київський національний університет імені Тараса Шевченка, 2016)
The signing of the Association Agreement between Ukraine and the European Union (EU) provides the implementation of European standards and norms in the different economic sectors and fields of activity in our country. The EU Water Framework Directive (WFD) is the main document in the area of water relations in the European Union among a number of water conservation directives. In the WFD emphasis on integrated water resources management by basin principle. With the participation of authors in 2013 was developed a method and performed modern hydrographic and water management delineation of territory of Ukraine. Under the proposed hydrographic delineation and according to the requirements of Water Framework Directive (WFD) in the Ukraine distinguish 9 river basins districts: the Vistula (Western Bug and San); Danube; Dniester; Southern Bug; Dnieper; rivers of the Black Sea; Don; Azov rivers; Crimea rivers. The area of the Vistula river basin (Western Bug and San rivers) are cross-border, covers the territory of three countries - Ukraine, Poland and Belarus. The result of this study is testing the river typology on the catchment area and lakes on the area of water surface under the Water Framework Directive of the European Union to assess the hydrographic network of the Vistula river basin (Western Bug and San) in Ukraine. The analysis of the basin river network showed that from the total number of river in the Vistula basin in Ukraine (total 3115 rivers) small river represent 98.5% (according to the typology WFD). The vast majority of them - 2999 of 3068 or 97.8% - are rivers with a length not exceeding 10 km. The average rivers in the basin are only 1.25%. The share of large and very large rivers of the total number of river, respectively, 0.2 and 0.05%. In the basin of the Western Bug in Ukraine: the large river - Poltva, Rata, Luga, Ryta; very large - Western Bug. In the basin of the San in Ukraine: the large river - Vyshnia, Zavadivka (Liubachivka); very large - San. Of the 68 lakes that are within the Ukrainian part of the basin of the Western Bug, the vast majority (48 lakes or 70.6%) is classified as very low. Small and average lakes are 9 (13.3% of the total number), there are two large lakes (Svitiaz and Pulemetske) - 3.0%. All natural lakes within the Ukrainian part of the basin San are classified as very small, with area less than 0.5 km2 .
Assessment of the hydrographic network of the Vistula river basin (Western Bug and San) in Ukraine according to the typology of EU Water Framework Directive
Keywords: Водна рамкова директива ЄС; річка; озеро; типологія; Water Framework Directive of the European Union; typology; river; lake